2013
DOI: 10.11158/saa.18.2.8
|View full text |Cite
|
Sign up to set email alerts
|

New Zealand species of <i>Oribotritia</i> (Acari: Oribatida: Oribotritiidae): descriptions of two new species and a key to eight species

Abstract: The genus Oribotritia (Acari: Oribatida: Oribotritiidae) was represented in New Zealand by six species prior to this work. In this paper, three species of Oribotritia from New Zealand are described, including two new species, Oribotritia mangamuka sp. nov. and Oribotritia bilaminae sp. nov., and a known species with some variation. A key to all known species of Oribotritia in New Zealand is also provided.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2014
2014
2018
2018

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 9 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…This work is part of our continuing study on New Zealand ptyctimous mites (Acari, Oribatida) (e.g. Liu & Zhang 2013a, b, c, d, e, 2014a, b, c, d, 2015a, b, c, 2016a. In a recent study of oribatid mite material from New Zealand Arthropod Collection, we identified two new species of the genus Austrophthiracarus from the North Island of New Zealand.…”
Section: Introductionmentioning
confidence: 99%
“…This work is part of our continuing study on New Zealand ptyctimous mites (Acari, Oribatida) (e.g. Liu & Zhang 2013a, b, c, d, e, 2014a, b, c, d, 2015a, b, c, 2016a. In a recent study of oribatid mite material from New Zealand Arthropod Collection, we identified two new species of the genus Austrophthiracarus from the North Island of New Zealand.…”
Section: Introductionmentioning
confidence: 99%